Mathematical theories of economic growth - Burmeister, Edwin; Dobell, A. Rodney (London : Macmillan, 1970)
This book is on growth theory and growth models ,the equation of motions for an economic system
Includes bibliographical references and index.
oo 07/11/2018
Loans
Keywords: Economic development